Analisis Manajemen Risiko Gangguan Internet Akibat Cuaca Ekstrem Terhadap Pembelajaran Daring di Kota Padang - Anggun Lisa Marianti; Meta Afra Niska; Miftahul Husni; Viony Dwi Arfa (Journal Educational Research and Development | E-ISSN : 3063-9158, 2025)
This study analyzes risk management of internet disruptions caused by extreme weather on online learning in Padang City. Using a qualitative approach with literature study methods, this research examines the types of risks, causal factors, impacts, and mitigation strategies. The findings reveal that extreme weather, particularly Tropical Cyclone Seed 95B, negative Indian Ocean Dipole (IOD), and peak rainy season, caused significant internet disruptions affecting students, teachers, and educational institutions. Students experienced learning delays, decreased concentration, and psychological stress. Teachers faced increased workload in preparing alternative materials and limited interaction with students. Schools encountered difficulties in managing schedules, administration, and educational innovation. The study emphasizes the importance of local policies that strengthen telecommunication infrastructure, cross-sector collaboration, and digital literacy to maintain learning continuity. This research provides comprehensive insights into internet disruption risk management and offers strategic recommendations for educational resilience in regions prone to extreme weather.